The influence of gaze direction on time perception: From the perspective of social perception - Ren, Weicong; Guo, Xiujuan; Huang, Jinfeng; Liu, Qingjun; Zhang, Zhijie (Frontiers in Psychology, 2023)
Gazing is important during communication, which is a type of body language that differs from culture to culture. The present study investigated the influence of direct and averted gaze directions on the perceived duration of gazing among same-race and other-race faces. The gaze direction effect, in which direct-gazing faces were perceived to be longer than averted-gazing faces were, was found in the same-race condition but not in the other-race condition. The results could promote our understanding of the underlying mechanism of the gaze direction effect based on the perception of interpersonal social interaction.